The increasing incidence of foetal echogenic congenital lung malformations: an observational study. (4th November 2014) - Stocker, Linden J.; Wellesley, Diana G.; Stanton, Michael P.; Parasuraman, Rajeswari; Howe, David T.
Abstract Objectives The aim of this study was to investigate the incidence of congenital lung malformations over the past 19 years. Congenital lung malformations (CLM) are a heterogeneous group of lung abnormalities. The antenatal diagnosis is important for foetal and neonatal management but there have been no studies examining whether the reported incidence of this abnormality is constant. Methods A retrospective cross‐sectional study of cases identified from the Wessex Antenatally Detected Anomalies (WANDA) register 1994–2012. Results One hundred and thirty‐three cases of CLM in 524 372 live and stillbirths were identified. All but seven were identified on antenatal ultrasound. During the early registry (1994–1998) the average incidence of CLM was 1.27 per 10 000 births. By the last 4 years (2008–2012) this had risen to 4.15 per 10 000 births, with a progressive increase during the intervening years. Conclusion There was over a three‐fold increase in the antenatally detected CLM in the Wessex region 1994–2012. Comparison with the antenatal detection of diaphragmatic hernia suggests that this is a true rise in incidence rather than an artefactual increase due to increased antenatal recognition secondary to improved ultrasound resolution and operator experience. These results have clinical and cost implications for practitioners of foetal medicine, neonatology and paediatric surgery services. © 2014 John Wiley & Sons, Ltd.